Behavioral and multimodal neuroimaging evidence for a deficit in brain timing networks in stuttering: a hypothesis and theory - Etchell, Andrew C.; Johnson, Blake W.; Sowman, Paul F. (Frontiers in Human Neuroscience, 2014)
The fluent production of speech requires accurately timed movements. In this article, we propose that a deficit in brain timing networks is the core neurophysiological deficit in stuttering. We first discuss the experimental evidence supporting the involvement of the basal ganglia and supplementary motor area in stuttering and the involvement of the cerebellum as a mechanism for compensating for the neural deficits that underlie stuttering. Next, we outline the involvement of the right inferior frontal gyrus as another putative compensatory locus in stuttering and suggest a role for this structure in an expanded core timing-network. Subsequently, we review behavioral studies of timing in people who stutter and examine their behavioral performance as compared to people who do not stutter. Finally, we highlight challenges to existing research and provide avenues for future research with specific hypotheses.